CRIMINAL AND LEGAL PROTECTION OF PATIENT AUTONOMY IN UKRAINE - Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: analysis of the phenomenon of «patient autonomy» as an object of criminal law protection. The methodological basis of the study is general scientific methods of cognition, with which the author solves the problem of the content of the patient autonomy and the possibility of criminal protection of this phenomenon. Results: the author emphasizes the need for a criminal study of patient autonomy and its individual components to unify criminal law terminology. Discussion: the author states that at the legislative level the issue of regulating the patient autonomy is resolved, but there are significant shortcomings in the practice of applying a number of articles of the Criminal Code of Ukraine in the field of medical activities. The problem of criminal legal protection is solved at the legislative level. There are a number of corpus delicti in the Criminal Code of Ukraine, the commission of which leads to a violation of the patient autonomy, but in this case there are several issues that will make the fight against crime in the medical field more effective. First, the problem of violation of the patient autonomy should be considered not only in legal but also in social terms. This applies to the patient-physician relationship, where the physician plays a leading role. In addition, the content of these relations lies not only in the profession, but also in the bioethical plane. Secondly, the terminology should be unified and the term «patient» should be used instead of the term «sick man». Thirdly, the statistics on the practice of application of the relevant norms, which are given in the article, show the high latency of these crimes. All these factors indicate a certain imperfection of the protection of the patient autonomy, including at the level of criminal law.